An empirical analysis of informal human capital investments in adolescence as a predictor of life outcomes - Stebbins, Richard Adiger (Kansas State University, 2019)
Human capital theory is used to predict life outcomes; it also examines an individual’s economic value, how to increase that value, and when the return on the investment in human capital no longer exceeds the investment cost (Becker, 1985; Weiss, 1995). Human capital investments are defined as any investment of time, money, or both that can change the economic value of the individual. This dissertation further distinguishes between formal and informal human capital investments. One of the most common formal investments in research literature uses higher education to predict future or expected earnings. Informal human capital investments are viewed here as those investments made outside a structured educational environment. Formal investments in human capital have been investigated globally using large samples with strict controls for potentially influencing variables, and the results consistently suggested that those with a college education receive greater lifetime earnings than those with no college education. Indeed, with factory jobs disappearing, a college education is often a required qualification to apply for a job today. Little research, however, has been done to investigate the potential impact of informal human capital investments. The purpose of this study was to investigate the potential impact of informal human capital investments made outside of the K-12 curriculum required for youth in the Unites States of America. Using longitudinal data from the National Longitudinal Study of Youth 1997, this study examined the potential impact of three informal human capital investments made in adolescence on four life outcomes for those youths. Informal human capital investments outside of the classroom were measured by (1) the minutes youths spent reading for pleasure, (2) taking extra lessons, or (3) watching television. The four life outcomes examined were (1) educational attainment, (2) wages, (3) employment status, and (4) cognitive ability. The data were analyzed using several hierarchical regressions to assess the impact of these informal human capital investments made in adolescence. The results showed that time spent reading for pleasure as an adolescent was statistically significantly and positively associated with educational attainment, increased cognitive ability, and likelihood of being employed, but was statistically significantly and negatively associated with slightly lower wages. Investing in informal human capital through extra lessons was statistically significantly and positively associated with educational attainment, employment, and cognitive ability. Watching television was statistically significantly and negatively associated with educational attainment and cognitive ability, but was statistically significantly and positively associated with wages when including respondents with zero hours worked.
Keywords: Human capital